Evaluasi Implementasi Sistem Manajemen Mutu ISO 9001:2008 di SMK Muhammadiyah Prambanan Yogyakarta - muhsin; Mulyanto Mulyanto (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the implementation of the ISO 9001:2008 QMS, analyze the supporting factors, inhibiting factors, and efforts made to overcome obstacles in the implementation of the ISO 9001:2008 QMS implementation at SMK Muhammadiyah Prambanan Yogyakarta. This type of research is a qualitative research using observation, documentation, and interview techniques. The population in this study were principals, teachers, and administration. The evaluation used uses the evaluation of the stake model. Based on the results of the research conducted, it can be seen that the implementation of the ISO 9001:2008 Quality Management System in SMK Muhammadiyah Prambanan is categorized as good once or running effectively. The supporting factors include teachers who have S1 and have received educator certificates, solid management, adequate infrastructure, large number of students and have many achievements, transparently managed finances, the existence of ISO 9001:2008 QMS guidelines, the desire of the parties involved. schools to improve service quality. Inhibiting factors include government policies that change frequently so that they affect the implementation of school curricula, there are still many students whose tuition payments are in arrears even until graduation, and there are still teachers who do not understand the ISO 9001:2008 QMS; Efforts made include socializing ISO to all school residents, making continuous improvements by always conducting periodic evaluations, the ISO team always trying to provide input to school management, optimizing the implementation of the Quality Management System with hard work, working smart and sincerely, improving and complete all deficiencies in the infrastructure data base, and increase cohesiveness among all school members. Keywords: Evaluation, Implementation, QMS ISO 9001:2008.